Pyroptosis-Related Signature as Potential Biomarkers for Predicting Prognosis and Therapy Response in Colorectal Cancer Patients - Li, Zhiyong; Liu, Yang; Lin, Baiqiang; Yan, Wei; Yi, Huijie; Wang, Haoran; Wei, Yunwei (Frontiers in Genetics, 2022)
Background: Abnormal mucosal inflammation is a critical risk factor for pathogenesis and progression in colorectal cancer (CRC). As a type of proinflammatory death, pyroptosis can recast a suitable microenvironment to promote tumor growth. However, the potential role of pyroptosis in CRC remains unclear. Methods: 38 pyroptosis related genes (PRGs) expression profiles and clinical information were collected from multiple public datasets. Bioinformatics methods were used to analyze the clinical significance, functional status, immune infiltration, genomic alteration, and drug sensitivity in different subgroups. RNA-seq analysis was used to analyze the regulation of gut microbiota on the expression of PRGs. Results: We obtained 6 PRGs signature through differential expression analysis, Unicox and Lasso regression analysis, and then constructed a risk prognosis model for predicting overall survival (OS) and recurrence-free survival (RFS). There were significant differences in clinical characteristics, 22 immune cells, and immune functions between the high- and low-risk groups. In addition, the PRGs signature were significantly associated with the microsatellite instability (MSI), tumor mutation burden (TMB), cancer stem cell (CSC) index, immunotherapeutic characteristics, and chemotherapeutic drug sensitivity. Moreover, the vitro experiments had shown that Fusobacterium nucleatum (F.n) could affect CASP6 expression, which was associated with the chemoresistance to 5-fluorouracil (5-Fu) in CRC. Conclusions: our findings provided a foundation for future research targeting pyroptosis and a new insight into the prognosis and immune cells infiltration of CRC, and they suggested that F.n might influence CRC progression through pyroptosis.